The Effect of Walled Nano-Carbon on the Physical, Thermal and Mechanical Properties of Epoxy - Hussein, Rasha Mohammed (Al-Khwarizmi Engineering Journal, 2018)
The physical, the thermal and the mechanical properties of Nano-composites, that consisted of Polyprime EP epoxy that reinforced by multi-walled carbon nanotubes (MWCNTs), have been studied. Various loading ratios, 0.1, 0.5, and 1 wt. %of MWCNT shave been infused into epoxy by a magnetic stirrer and then the hardener mixed with the mthat supplied with the epoxy. All sample shave been cutting using CNC machine. Tensile test, three-point bending, hardness tests, lee’s disk, differential scanning calorimetry, water absorption and dielectric and electrical conductivity test were utilized on unfilled, MWCNT-filled epoxy to identify the loading effect on the properties of materials. Scanning electron microscopy (SEM) was used to determine the dispersion case of nanotubes in the base matrix. The tensile test results showed an improvement in Young’s modulus with higher MWCNT addition percentages. The highest value of the tensile strength was obtained at 0.5 wt.% of MWCNT with increasing ratio 66.7%. The values of the Shore D hardness tests are slightly increases as the filler percentage increased, and the maximum value was observed at MWCNT weight percent of 4.4. Images of SEM showed that the specimen of 0.1 wt.% MWCNT has less voids as compared with other specimen. Thermal conductivity and glass transition temperature increase when the loading ratio increased the maximum increasing at 1wt% with 120% and 23% respectively. The true density and electrical conductivity increase when nano carbon infused but decreasing in the dielectric constant and water absorber.